Flocculation of Chlamydomonas reinhardtii with Different Phenotypic Traits by Metal Cations and High pH - Fan, Jianhua; Zheng, Lvhong; Bai, Yunpeng; Saroussi, Shai; Grossman, Arthur R. (Frontiers in Plant Science, 2017)
Concentrating algal cells by flocculation as a prelude to centrifugation could significantly reduce the energy and cost of harvesting the algae. However, how variation in phenotypic traits such as cell surface features, cell size and motility alter the efficiency of metal cation and pH-induced flocculation is not well understood. Our results demonstrate that both wild-type and cell wall-deficient strains of the green unicellular alga Chlamydomonas reinhardtii efficiently flocculate (>90%) at an elevated pH of the medium (pH 11) upon the addition of divalent cations such as calcium and magnesium (>5 mM). The trivalent ferric cation (at 10 mM) proved to be essential for promoting flocculation under weak alkaline conditions (pH ~8.5), with a maximum efficiency that exceeded 95% and 85% for wild-type CC1690 and the cell wall-deficient sta6 mutant, respectively. Near complete flocculation could be achieved using a combination of 5 mM calcium and a pH >11, while the medium recovered following cell removal could be re-cycled without affecting algal growth rates. Moreover, the absence of starch in the cell had little overall impact on flocculation efficiency. These findings contribute to our understanding of flocculation in different Chlamydomonas strains and have implications with respect to inexpensive methods for harvesting algae with different phenotypic traits. Additional research on the conditions (e.g. pH and metal ions) used for efficient flocculation of diverse algal groups with diverse characteristics, at both small and large scale, will help establish inexpensive procedures for harvesting cell biomass.